Interest rate spreads and forward guidance - Christian Bredemeier; Christoph Kaufmann; Andreas Schabert (European Central Bank (ECB), 2018)
We provide evidence that liquidity premia on assets that are more relevant for private agents' intertemporal choices than near-money assets increase in response to expansionary forward guidance announcements. We introduce a structural specification of liquidity premia based on assets' differential pledgeability to a basic New Keynesian model to replicate this finding. This model predicts that output and inflation effects of forward guidance do not increase with the length of the guidance period and are substantially smaller than if liquidity premia were neglected. This indicates that there are no puzzling forward guidance effects when endogenous liquidity premia are taken into account.
Keywords: E32; E42; E52; 330; Forward guidance; Unconventional monetary policy; Liquidity premium